Genetic and physical analyses of the growth rate-dependent regulation of Escherichia coli zwf expression. - Rowley, D L (1991)
Growth rate-dependent regulation of the level of Escherichia coli glucose 6-phosphate dehydrogenase, encoded by zwf, and 6-phosphogluconate dehydrogenase, encoded by gnd, is similar during steady-state growth and after nutritional upshifts. To determine whether the mechanism regulating zwf expression is like that of gnd, which involves a site of posttranscriptional control located within the structural gene, we prepared and analyzed a set of zwf-lacZ protein fusions in which the fusion joints are distributed across the glucose 6-phosphate dehydrogenase coding sequence. Expression of beta-galactosidase from the protein fusions was as growth rate dependent as that of glucose 6-phosphate dehydrogenase itself, indicating that regulation does not involve an internal regulatory region. The level of beta-galactosidase in zwf-lac operon fusion strains and the level of zwf mRNA from a wild-type strain increased with increasing growth rate, which suggests that growth rate control is exerted on the mRNA level. The half-life of the zwf mRNA mass was 3.0 min during growth on glucose and 3.4 min during growth on acetate. Thus, zwf transcription appears to be the target for growth rate control of the glucose 6-phosphate dehydrogenase level.